A psychometric evaluation of the applicability of LibQUAL+® in a developing country perspective in Bangladesh. Issue 3 (7th December 2022) - Ahmed, S.M. Zabed; Shoeb, Md. Zahid Hossain
Abstract : Purpose: The purpose of this paper is to assess the psychometric validity of the LibQUAL+® instrument in a developing country context in Bangladesh. Design/methodology/approach: This study adopted a paper-version of the original LibQUAL 22 core-items to survey library users' perceptions of minimum, desired and perceived levels of service quality of university libraries in Bangladesh. The survey accumulated a total of 544 valid responses over a period of two weeks. The means and standard deviations for each service item were computed for the three service levels. The confirmatory factor analysis (CFA) was used to test the original three-factorial structure and to assess the psychometric validity of the LibQUAL instrument. A one-factor CFA and separate CFAs by gender and user group on perceived services were conducted to determine the original three-factor structure of LibQUAL scale. Exploratory factor analyses (EFAs) were also performed on the perceived scores to examine the potential factor structure of the scale. The descriptive statistics including EFAs and the CFA models were performed through IBM® SPSS® Statistics and IBM® SPSS® Amos, respectively. Findings: The findings of this paper showed that all perceived services fell below the minimum scores. The confirmatory factor analyses found poor model fits for the original three-factor solution of the LibQUAL scale. The EFA results also showed no factorial structure similar to the original LibQUAL dimensions. The findings exhibited a low psychometric quality of LibQUAL in academic library settings in Bangladesh. Originality/value: This study is the first of its kind to empirically examine the psychometric validity of the LibQUAL scale in a developing country perspective in Bangladesh.